A Simple Gaussian Measurement Bound for Exact Recovery of Block-Sparse Signals - Zhi Han; Jianjun Wang; Jia Jing; Hai Zhang (Discrete Dynamics in Nature and Society)
We present a probabilistic analysis on conditions of the exact recovery of block-sparse signals whose nonzero elements appear in fixed blocks. We mainly derive a simple lower bound on the necessary number of Gaussian measurements for exact recovery of such block-sparse signals via the mixed l2/lq  (0<q≤1) norm minimization method. In addition, we present numerical examples to partially support the correctness of the theoretical results. The obtained results extend those known for the standard lq minimization and the mixed l2/l1 minimization methods to the mixed l2/lq  (0<q≤1) minimization method in the context of block-sparse signal recovery.